2001
DOI: 10.1093/emboj/20.23.6761
|View full text |Cite
|
Sign up to set email alerts
|

Two distinct effects on neurotransmission in a temperature-sensitive SNAP-25 mutant

Abstract: contributed equally to this work Vesicle fusion in eukaryotic cells is mediated by SNAREs (soluble N-ethylmaleimide-sensitive factor attachment protein receptors). In neurons, the t-SNARE SNAP-25 is essential for synaptic vesicle fusion but its exact role in this process is unknown. We have isolated a SNAP-25 temperature-sensitive paralytic mutant in Drosophila, SNAP-25 ts . The mutation causes a Gly50 to Glu change in SNAP-25's ®rst amphipathic helix. A similar mutation in the yeast homologue SEC9 also result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
40
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(42 citation statements)
references
References 47 publications
2
40
0
Order By: Relevance
“…6B), consistent with a TS impairment of trans-SNARE complex formation associated with synaptic vesicle priming. Previous studies of SNAP-25 TS indicate that synaptic vesicle docking at active zones is not disrupted at larval neuromuscular synapses, and that in vivo levels of SDS-resistant (likely cis) SNARE complexes are not altered in this mutant (22). Finally, it will be of great interest to further investigate the relationship of SNAP-25-dependent mechanisms underlying fast and slow components of recovery.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…6B), consistent with a TS impairment of trans-SNARE complex formation associated with synaptic vesicle priming. Previous studies of SNAP-25 TS indicate that synaptic vesicle docking at active zones is not disrupted at larval neuromuscular synapses, and that in vivo levels of SDS-resistant (likely cis) SNARE complexes are not altered in this mutant (22). Finally, it will be of great interest to further investigate the relationship of SNAP-25-dependent mechanisms underlying fast and slow components of recovery.…”
Section: Discussionmentioning
confidence: 83%
“…Studies of a TS SNAP-25 mutant, SNAP-25 TS , identified a missense mutation within the N-terminal half of the first SNARE helix, which disrupts specific aspects of SNAP-25 function (see ref. 22 and Discussion). The present study builds on previous analysis of synaptic transmission in Drosophila (23) by revealing conserved properties of short-term synaptic depression at adult neuromuscular synapses and employing these conditional mutants to examine the underlying molecular determinants.…”
mentioning
confidence: 81%
“…Primary rat hippocampal neuron cultures were plated on coverslips that were fixed for 10 min in freshly prepared 4% paraformaldehyde and processed as above. Primary antibodies and dilutions were as follows: mouse anti-Chaoptin (24B10), 1:50; mouse antiSynapsin (3C11), 1:50; mouse anti-Dlg (4F3), 1:50; mouse anti-CSP (6D6), 1:50; mouse anti-Bruchpilot (nc82), 1:100; mouse anti-SV2, 1:50 (Developmental Studies Hybridoma Bank, University of Iowa, Iowa City, IA); rabbit anti-Synaptotagmin (Littleton et al, 1993), 1:2000; rabbit anti-SNAP-25 (Rao et al, 2001), 1:200; mouse anti-Golgi (7H6D7C2) (Stanley et al, 1997) (345867; Calbiochem, La Jolla, CA), 1:500; rabbit anti-DsRed (recognizes tdTomato) (632496; Clontech, Mountain View, CA), 1:1000; rabbit anti-GFP-Alexa 488 (recognizes YFP) (Invitrogen, San Diego, CA; A-21311), 1:250; rat anti-neuronal synaptobrevin (Wu et al, 1999), 1:250. Secondary antibodies were as follows: goat anti-mouse Cy3 and goat anti-rabbit Cy3 (Jackson ImmunoResearch, West Grove, PA), and goat anti-mouse Alexa 488 and goat anti-rat Alexa 647 (Invitrogen).…”
Section: Methodsmentioning
confidence: 99%
“…Similar to Df(1)446-20 larvae, temperature-sensitive SNAP-25 (SNAP-25 ts ) larvae show increased mini-EJP frequency at 22 °C with no differences in mini-EJP amplitude. 45 The authors suggested that the SNAP-25 ts mutation may yield more fusionready SNARE complexes, thus increasing the frequency of vesicle fusion. 45 The phenocopy of this mutation by a null Ppt1 mutation may be associated with a dysregulation of SNAP-25 palmitoylation, leading to an increase in membrane-associated, palmitoylated SNAP-25 following vesicle release.…”
Section: Connections To Substratesmentioning
confidence: 99%
“…45 The authors suggested that the SNAP-25 ts mutation may yield more fusionready SNARE complexes, thus increasing the frequency of vesicle fusion. 45 The phenocopy of this mutation by a null Ppt1 mutation may be associated with a dysregulation of SNAP-25 palmitoylation, leading to an increase in membrane-associated, palmitoylated SNAP-25 following vesicle release. This might produce an increase in spontaneous fusion events, as exemplified by the increase in mini EJPs.…”
Section: Connections To Substratesmentioning
confidence: 99%